Training, Supervision, and Competence Assessment of Cameroonian Health Care Providers Using HPV Self-Sampling, Triage by Visual Inspection, and Treatment by Thermal Ablation in a Single Visit - Chloé Frund; Bruno Kenfack; Jessica Sormani; Jessica Sormani; Ania Wisniak; Jovanny Tsuala Fouogue; Eveline Tincho; Tania Metaxas; Pierre Vassilakos; Pierre Vassilakos; Patrick Petignat (Frontiers Media S.A., 2022)
BackgroundDeveloping human resource capacity and efficient deployment of skilled personnel are essential for cervical cancer screening program implementation in resource-limited countries. Our aim was to provide a context-specific training framework, supervision, and effectiveness evaluation of health care providers in a cervical cancer screening program.MethodsA 5-year cervical cancer screening program was implemented in Dschang, West Cameroon. Women were invited to perform human papillomavirus self-sampling (Self-HPV), followed by triage using visual inspection with acetic acid (VIA) and thermal ablation if needed. Health care providers were trained in four key learning phases to perform counseling, screening, and treatment process in a single visit. Training included (i) a 3-day basic course, (ii) 3-day advanced practical training, (iii) 2 weeks of supervision, and (iv) bi-monthly supervision by a mentor. The diagnostic performance of health care providers was compared between two time periods, period I (September 2018 to April 2019) and period II (May 2019 to January 2020), for an overall 17-month study period.ResultsFourteen health care providers were recruited for the training course and 12 of them completed the training objectives. Follow-up and evaluations were conducted for three health care providers working in the screening unit at Dschang District Hospital. During the study period, 1,609 women performed Self-HPV, among which 759 were screened during period I and 850 during period II. HPV positivity was 18.2 and 17.1%, and VIA positivity was 45.7 and 71.0% in period I and II, respectively. VIA sensitivity was 60.0% (95% confidence interval [CI] 26.2-87.8) and 80.8% (95% CI 60.6-93.4) in period I and II, respectively (p = 0.390). VIA specificity decreased between period I (57.4, 95% CI 48.1-66.3) and II (30.8, 95% CI 22.6-40.0) (p < 0.001). Health care providers demonstrated substantial agreement with their mentor in their diagnoses during both periods (period I: Cohen's kappa coefficient [k] = 0.73, 95% CI 0.62-0.85, and period II: k = 0.62 0.47-0.76; p = 0.0549).DiscussionTraining, supervision, and a focus on effectiveness in cervical cancer screening are interventions that contribute to improving frontline provider competencies and maintaining a high quality of health care service delivery.